2005
DOI: 10.1021/jp047240b
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Decompositions and Physical Properties of Decomposition Compounds in Li-Ion Battery Electrolytes Studied by DFT Calculations and Molecular Dynamics Simulations

Abstract: The density functional theory (DFT) calculations have been performed for the reduction decompositions of solvents widely used in Li-ion secondary battery electrolytes, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonates (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), including a typical electrolyte additive, vinylene carbonate (VC), at the level of B3LYP/6-311+G(2d,p), both in the gas phase and solution using the polarizable conductor calculation model. In the gas phase, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 80 publications
5
137
1
Order By: Relevance
“…60,65 This was also confirmed by electron paramagnetic resonance spectroscopy measurement. 19,[74][75][76][77] and some key liquid properties (such as density, cohesive energy, solubility in the solvent) of SEI components, which will be discussed in the section "Correlation of SEI properties with battery performance, starting from known components".…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…60,65 This was also confirmed by electron paramagnetic resonance spectroscopy measurement. 19,[74][75][76][77] and some key liquid properties (such as density, cohesive energy, solubility in the solvent) of SEI components, which will be discussed in the section "Correlation of SEI properties with battery performance, starting from known components".…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…First, every solvent and salt species will decompose at its unique voltage. Tasaki 74 found that the order for the solvent molecule to undergo the first electron reduction is EC > PC > VC > DMC > EMC > DEC, with EC being the most likely to be reduced. VC, on the other hand, is most likely to undergo the second electron reduction, followed by EC and PC, as VC > EC > PC.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although extensive studies of solid/electrolyte (SEI) formation and stability on graphite anodes, as well as reactions involving LiCoO 2 cathodes, have been completed, SEI formation on graphite cathodes due to anion intercalation has not been examined. Since the intercalation process strongly depends on processes at the electrode-electrolyte interface [17], heterogeneity and composition differences on electrode surfaces are expected to significantly influence capacity and cycling efficiencies. Certain functional groups can be introduced onto carbon surfaces via high-temperature treatments, air oxidation, plasma and gas treatment, and wet chemistry reactions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…94,105 Classical MD simulations have also been used to investigate the structure of carbonate based electrolytes doped with lithium salts, most commonly LiPF 6 , at graphitic interfaces. 97,[109][110][111][112] Vatamanu et al found that the composition of the electrolyte interfacial layer depended strongly on the electrode potential. The amount of EC and DMC at the interface increased as the electrode charge was increased, for both positively and negatively charged electrodes.…”
Section: Simulations Of Electrolytes At Graphene Interfacesmentioning
confidence: 99%